Analisis kemampuan pemecahan masalah dalam menyelesaikan soal pada materi SPLDV ditinjau dari kemampuan berpikir kreatif siswa (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
Mathematical problem solving is an activity carried out by someone in solving a problem to get a solution. According to Polya, the stages of problem solving are understanding the problem, devising a plan, carrying out the plan, and looking back. The purpose of this study was to analyze students 'problem solving abilities in solving problems based on students' creative thinking abilities. This type of research is descriptive qualitative. The subjects of this study were students of class VIII SMP N 1 Cluwak. Subjects were determined using a creative thinking ability test. Data collection techniques in this study used written data in the form of mathematical problem solving tests and interviews with each subject. From the results of research using triangulation methods show that: (1) subject with very creative thinking skills are able to meet all problem solving indicators; (2) subject with quite creative thinking skills do not looking back the answers; and (3) subject with not creative thinking skills do not looking back answers and tend to be less careful in solving problems.
Keywords: problem solving ability; creative thinking